IMPLEMENTASI PROGRAM BEING IN ASIA DI INDONESIA OLEH UNITED NATIONS DEVELOPMENT PROGRAMME (UNDP) - Sofyan, Muhammad; Retnaningsih, Umi Oktyari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The obligation to fulfil human rights is a duty of a State. Human rights are the legal rights of every human being of a universal nature. The human rights issue is growing with the high rate of globalization and then there is a pervasiveness of gender minorities in this case: Lesbian, Gay, Bisexual, Transgender (LGBT). Many LGBT groups in Indonesia have suffered from violence, discrimination and human rights violations, and this is happening because in Indonesia there are no LGBT regulations. In this issue UNDP provides assistance to the LGBT community in Indonesia, through the Being LGBT in Asia program UNDP strives to address inequalities, violence, stigma and discrimination based on a person's sexuality and gender identity. This research uses a qualitative method with a secondary data source, the library research. The result of this study is the role of UNDP in the fight for the rights of the LGBT community in Indonesia. Keywords: LGBT, Being LGBT in Asia, HAM, UNDP